Dosimetric evaluation for treatment using radiochromic films - Orbegoso, Carlos (2009)
In radiotherapy one of the biggest problems that arises is the uncertainty in the measurement of the dose absorbed by the tumorous and healthy tissue a dosimeter appropriated for dosimetry measurement are the radiochromic films. This work there as objective dose adsorbed evaluate with radiochromic films GafChromic MD-55-2, which were characterized and calibrated. There was designed the geometry of the ocular implant for then to measure the dose for different positions relative to the axial axis of the applicator. The results will be confirmed with values obtained by the technology TLD and by values given by the System of Planning Prowess 3000 version 3.06. Dosimetry for radiochromic films they reproduce the values of dose obtained by the methods of planning in Prowess and dosimetría TLD with relative minor differences to the 1 % and 6 %, respectively. For it, the radiochromic films turn into a very valuable tool to be able to realize with enough precision and accuracy the dosimetry of ocular brachyterapy.